2020
DOI: 10.1097/meg.0000000000001892
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative systemic biomarkers predict post-liver transplantation acute kidney injury

Abstract: Objective Liver transplant (LT) is a definitive therapeutic option for patients with chronic liver disease. However, acute kidney injury after LT (post-LT AKI) is a frequent complication that may lead to graft dysfunction and decrease life expectancy. Delay in AKI detection by traditional biomarkers boosted research with new biomarkers for post-LT AKI as neutrophil gelatinase-associated lipocalin (NGAL) and syndecan-1. We aim to evaluate associations of intraoperative systemic NGAL and syndecan-1 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…As expected, the surgical time of ELRA was selected as an independent risk factor for major postoperative complications. In 2020, Giustiniano et al 69 and Cezar et al 70 found that surgical time was associated with postoperative complications of liver resection and could predict acute kidney injury after liver transplantation, which is similar to our results. Therefore, we should strictly comply with aseptic principles and further improve our surgical efficiency to minimize postoperative complications.…”
Section: Discussionsupporting
confidence: 90%
“…As expected, the surgical time of ELRA was selected as an independent risk factor for major postoperative complications. In 2020, Giustiniano et al 69 and Cezar et al 70 found that surgical time was associated with postoperative complications of liver resection and could predict acute kidney injury after liver transplantation, which is similar to our results. Therefore, we should strictly comply with aseptic principles and further improve our surgical efficiency to minimize postoperative complications.…”
Section: Discussionsupporting
confidence: 90%
“…There have been shown that renal hypo-perfusion, surgery time and hemodynamic instability at intraoperative, systemic inflammatory response, along with the choice of antibiotics which have nephrotoxicity in the post-transplant period, were common aetiological factors (25,33,35,36). Risk factors for AKI in the pre-transplant period include syndecan-1 level, the level of serum NGAL, high vitamin B12, recipient age and C-reactive protein (CRP) (19,24,37,38). Although these clinical variables have provided predictive values in identifying the occurrence of AKI after LT, the additional use of specific serum biomarkers might further improve the ability to identify patients with AKI.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous study, the data associated with postoperative AKI after LT were collected (5,20,24,25). Baseline characteristics of patients were obtained including age, sex, body mass index (BMI), model for end-stage liver disease (MELD) score, Child-Pugh classification, aetiology for LT (tumor, viral disease, alcoholic or others), and history of hypertension, diabetes mellitus, coronary disease or infection, as well as use of diuretics and nephrotoxic drug including vancomycin, aminoglycosides, rifampicin, amphotericin B, immunosuppressants and chemotherapy, etc.…”
Section: Clinical Datamentioning
confidence: 99%
“…In general, NGAL measured within 2‐6 hours after reperfusion predicts post‐LT AKI, ( 77,81,82 ) although not in living donor LT. ( 76 ) Several studies report that change in, rather than absolute value of, NGAL was useful in predicting post‐LT AKI. ( 74,77,80,81,83,84 ) Among patients with AKI, uNGAL levels did not predict which patients will require renal replacement therapy. ( 85 )…”
Section: Role Of Novel Biomarkersmentioning
confidence: 99%
“…(73) Intraoperative and perioperative NGAL measurements show acceptable performance in predicting AKI (AUC > 0.7) in most studies. (74)(75)(76) NGAL may predict AKI after LT earlier than other biomarkers. (73) In 1 study, it peaked 19-28 hours (urine) and 12-23 hours (plasma) earlier than sCr.…”
Section: Kidney Biomarkers In Liver Transplantationmentioning
confidence: 99%